Occult HBV infection and HCC - Chemin, Isabelle (Iatreia, 2007)
A number of risk factors appear to play a role in Hepatocellularcinoma (HCC), HBV infection being one of the most important. Chronic inflammation and cytokines are key determinants in the development of fibrosis and liver cell proliferation. HBV DNA integration into host cellular DNA, has been extensively studied and may disrupt or promote expression of cellular genes that are important in cell growth and differentiation. Moreover, expression of HBV proteins may have a direct effect on cellular functions, and some of these gene products may lead to malignant transformation. Several HBV genes have been frequently found in infected tissues including truncated pre-S2/S, hepatitis B X gene, and a novel spliced transcript of HBV (hepatitis B spliced protein). The proteins expressed from these integrated genes have been shown to have intracellular activities, including effects on cellular growth and apoptosis. Occult hepatitis B virus (HBV) infection is characterized by persistence of HBV DNA into the tissue of hep atitis B surface antigen-negative individuals. The clinical relevance of this peculiar infection, in particular, the impact of occult HBV infection in cases of HCC has been a matter of debate. Prevalence and molecular status of occult HBV in patients with HCC has been investigated in several studies. HCC patients from Italy, France, Japan, Morocco, the United States, Canada etc…..who had no detectable HBsAg in their serum have been studied. In these HBsAg-negative HCC patients, HBV DNA was detected in tumorous and/or in adjacent non tumorous liver tissue using polymerase chain reaction (PCR) in almost half of the patients, being anti-HCV positive or not. Some of the patients are positive for anti-HBc antibodies as the only marker of HBV infection, but not all. Covalently closed circular HBV DNA may be detected indicating that at least some of these patients had actively replicating HBV infections. Observational cohort study showed that, among the HBsAg-negative patients with chronic hepatitis C, HCC develops for the most part in carriers of occult HBV. One of the markers in HCC cases, HBsAg (-), has been the presence of the HBV-X gene expression in HCC since positivity for the HBV-X protein in liver tissue in several studies reached half of the liver tissues specimens. In all studies, the significant association of occult HBV with HCC was irrespective of age, sex, and may be contemporary with hepatitis C virus infection. Both integrated viral DNA and covalently closed circular HBV genomes were detected in patients with occult HBV. Moreover, the presence of free HBV genomes was associated with persistence of viral transcription and replication: There are evidences that occult HBV is a risk factor for the development of HCC and that the potential mechanisms whereby overt HBV might induce tumour formation are mostly maintained in cases of occult infection